Factors Forming E-Service Satisfaction of PJP QRIS on Micro Business Merchants in Bandung City with E-Servqual Approach and E-Service Satisfaction Model - Dwiyanisa, Ashila; Larashati, Irena; Muthmainah, Freiti Cindy; Rachadi, Raden Ali Akbar; Nurdianti, Siti Sabrina (LPPM STMIK Mardira Indonesia, 2024)
This research aims to identify the factors shaping electronic service satisfaction (e-service satisfaction) among micro business merchants in Bandung City using QRIS payment service providers (PJP). The study employs the E-Servqual and E-Service Satisfaction Model. Data were collected through surveys from 330 respondents who are QRIS users in micro businesses. The analysis method used is Exploratory Factor Analysis (EFA) to identify the most influential dimensions of e-service quality impacting user satisfaction. The results indicate four main factors that influence e-service satisfaction: reliability, responsiveness, assurance, and overall satisfaction. The study also finds a high level of QRIS adoption among micro-business merchants, with a preference for non-bank service providers. The research recommends that QRIS providers continue enhancing service quality, particularly in terms of response speed, system security, and reliability, to improve customer satisfaction and merchant loyalty